Drawing the Veil of Sovereignty: Early Modern Islamic Empires and Understanding Sacred Kingship - Strathern, Alan (History and theory, 2014)
This article considers A. Azfar Moin, The Millennial Sovereign: Sacred Kingship and Sainthood in Islam, in the light of theories of sacred kingship and religious change. Although Muslim kingship has tended to be presented as an essentially secular institution, Moin is able to show how deeply divine images and understandings shaped kingship in both the Safavid and Mughal empires, which were bound together by mutual influence and competition. The divine matrix of kingship was facilitated by the influence of preeminent Sufism, Mongol universalism, millenarian technologies and dreams, and Persian tradition. The article suggests that the methodological approach adopted here, resembling l'histoire des mentalités, shows how our analyses of sacred kingship can be obscured by a focus on canonical and prescriptive texts. Taking up the theme of transgression, it compares Moin's work with recent anthropological reflections on the symbolism of the stranger-king. The article also uses Moin's work to indicate the problems with the critical dismissal of “legitimacy” as an indispensable (though insufficient) analytical tool. The subject matter is further placed within an overarching conceptualization of global religious diversity based on the tension between transcendentalist vs. immanentist impulses. In that light the reassertion of “transcendentalist” religiosity in the guise of an orthodox push-back against the enchanted cultural world re-imagined by Moin only appears in greater need of explanation. Avenues of comparative reflection are also opened up with Christian monarchy, which was both less profoundly “immanentized” in the early modern era and less successful at exporting itself in areas outside of imperial influence. The article concludes by considering the implications for theories of a global early modernity, and a comparison with Andre Wink's quite different characterization of Akbar as a secular-minded rationalist.